Drive-through Satellite Testing: An Efficient Precautionary Method of Screening Patients for SARS-CoV-2 in a Rural Healthcare Setting. (August 2020) - Molling, Paul E.; Holst, Tanner T.; Anderson, Benjamin G.; Fitzgerald, Kevin; Eddy, Megan; Weber, Bradley D.; Schwan, Brenda; Heiderscheit, Chris J.; Jagim, Andrew R.
The first documented case of COVID-19 in the United States occurred on January 30th, 2020. Soon after, a global pandemic was declared in March 2020 with each state issuing stay at home orders based on population, risk for community transmission and current number of positive cases. A priority for each region was to develop efficient systems for testing large patient volumes in a safe manner to reduce the risk of community transmission. A community based United States health care system in the upper mid-west implemented a drive through testing site in an attempt to divert suspected cases of COVID-19 away from larger patient areas while protecting staff and patients. This commentary outlines the planning, work flow and challenges of implementing this drive through testing site in a rural community setting.